Why are experienced users of WeChat likely to continue using the app?. Issue 4 (29th October 2018) - Gong, Xiuyuan; Liu, Zhiying; Zheng, Xiabing; Wu, Tailai
Abstract : Purpose: Mobile social apps permeate every facet of daily life through the pervasive use of smartphones. Customer retention with mobile social apps has become extremely important for app-related companies. The purpose of this paper is to explore why experienced users in mobile social apps (e.g. WeChat) are likely to continue using the app. Design/methodology/approach: This study proposed a conceptual model to identify key determinants of continuance intention of WeChat users and highlight the effects of individual experience. Data were collected from WeChat users, which is one of the most popular mobile social apps in China. The study employed partial least squares regression to test the research model based on a survey of 295 valid responses. Findings: Results showed that trust, which was driven by user satisfaction and perceived critical mass, played a critical role in influencing the continuance intention of WeChat users. Moreover, tie strength exerted a negative moderating effect on the relationship between trust and continuance intention. Specifically, tie strength and perceived critical mass had strong impacts on the continuance intention of low-experience users. In addition, the effect of frequency was closely associated with the continuance intention of high-experience users. Research limitations/implications: This study addressed the issue of mobile social app continuance intention by providing an innovative means to explore the key antecedents of user continuance intention from the experience perspective. The findings not only prove that trust plays a central role in influencing the continuance intention of experienced users but also reveal that the determinants of continuance intention vary among users with different experience. The results provide insights into the key antecedents of experienced WeChat user continuance intention and contribute to the literature on mobile social apps and individual differences. Practical implications: The results provide suggestions for mobile social app practitioners to effectively plan mobile social app retention practices and to set up appropriate incentive mechanisms for retaining users with different experiences. Originality/value: Although abundant studies have focused on the adoption of media users, few studies have investigated the post-adoption behavior of experienced users in the context of mobile social apps. This study revealed the key determinants of the continuance intention of WeChat users and pinpointed the different impacts of these antecedents on users with different levels of experience. It also provides useful guidelines for practitioners to effectively retain users with different levels of experience.